(untitled) (Scientific journal of the Fergana State University, 2026)
This work is devoted to the study of the influence of various methods of strength training on the development of jumping ability and speed qualities among students involved in volleyball. Traditional strength exercises, plyometrics and their combination were compared. The results showed a positive trend in all the parameters studied in all groups, which indicates the effectiveness of the methods used, but differences in the degree of exposure were found.